Overview of Family Support Towards Motivation to Quit Smoking in Students at SMK Makassar - Magdalena, Magdalena (Jurnal Perilaku Kesehatan Terpadu, 2022)
Smoke is serious problem _ Because its influence on various aspect , ie aspect health , aspect economic , aspect social . According to WHO (2008), there are 10 countries with the largest number of smokers in the world, one of which is Indonesia, which ranks third after China and India. In Indonesia, in 2014 the prevalence of smokers was 34.7%, in 2015 , the number smoker Indonesian population aged ?15 years has reached 36.3%. Objective study is For know description support family to motivation stop smoking among students at SMAK Makassar. Type study This is descriptive observational. Sample in study is student There are 44 people in class XI who smoke at SMAK Makassar technique total sampling. Research result show that of the 44 respondents studied , some big respondents get support family that is as many as 24 people (54.5%), and some big respondents who did not motivated For stop smoke that is as many as 26 people (59.1%). Concluded that the more Good support family to student will give motivation to they For can stop smoking . Recommended to nurse to get it give motivation to family in give support for teenagers No own habit cigarette . Nurses can too give education to danger smoking in adolescents.